Pengaruh Pengetahuan Etika dan Gender terhadap Persepsi Etis Mahasiswa Akuntansi dengan Love of Money Sebagai Variabel Intervening - Audri, Claristha Virzha; Putra, Wirmie Eka; Gowon, Muhammad (Ekonomis: Journal of Economics and Business, 2025)
This study aims to understand the influence of ethical knowledge and gender on the ethical perception of accounting students at Jambi University, both directly and with love of money as an intervening variable. The study used a survey method approach with quantitative analysis and primary data collection through questionnaires distributed online to accounting student respondents at Jambi University, class of 2020-2022. The study population was all accounting students of the class, with a sample of 100 students selected using the purposive sampling method based on certain characteristics. Data analysis was carried out using the SEM-PLS method through descriptive and quantitative statistical stages, and hypothesis testing using the bootstrapping technique by looking at the significance of the p-value. The results of the study prove that ethical knowledge and gender have a significant effect on the ethical perception of accounting students, where women tend to have better ethical perceptions than men. In addition, love of money has an impact on ethical perceptions, although it does not mediate the relationship between ethical knowledge, gender, and ethical perceptions. Individuals with a better understanding of ethics show a more balanced relationship with material things and less attachment to the pursuit of wealth. However, gender does not always correlate with money-related behavior.